Spatial and temporal variations of air pollution over 41 cities of India during the COVID‐19 lockdown period (2020)
In this study, we characterize the impacts of COVID-19 on air pollution using NO2 andAerosol Optical Depth (AOD) fromTROPOMI and MODIS satellite datasets for 41 cities in India. Specifcally, our results suggested a 13% NO2 reduction during the lockdown (March 25–May 3rd, 2020) compared to the prelockdown (January 1st–March 24th, 2020) period.Also, a 19% reduction in NO2 was observed during the 2020-lockdown as compared to the same period during 2019.The top cities where NO2 reduction occurred were New Delhi (61.74%), Delhi (60.37%), Bangalore (48.25%),Ahmedabad (46.20%), Nagpur (46.13%),Gandhinagar (45.64) and Mumbai (43.08%) with less reduction in coastal cities.The temporal analysis revealed a progressive decrease in NO2 for all seven cities during the 2020 lockdown period. Results also suggested spatial diferences, i.e., as the distance from the city center increased, the NO2 levels decreased exponentially. In contrast, to the decreased NO2 observed for most of the cities, we observed an increase in NO2 for cities in Northeast India during the 2020 lockdown period and attribute it to vegetation fres.The NO2 temporal patterns matched theAOD signal; however, the correlations were poor. Overall, our results highlight COVID-19 impacts on NO2, and the results can inform pollution mitigation eforts across diferent cities of India.